Association between intention for physical activity practice, social support and physical activity - Hermes Koller de Paiva; Edina Maria de Camargo; Alexandre Augusto de Paula da Silva; Rodrigo Siqueira Reis (Universidade Federal de Santa Catarina, 2016)
Intrapersonal and interpersonal aspects have been widely correlated to variations on the physical activity (PA) levels. The aim of this study was to examine the moderating effect of intention for PA practice on the association between social support and leisure PA levels in a sample of college students from Curitiba, Brazil. A questionnaire was administered in a sample of 349 college students from a Physical Education undergraduate program. The variables intention to PA practice, social support (family and friends) and leisure-time PA were obtained through interviews. Poisson regression was used to test the moderating effect of intention to PA practice on the association between social support and leisure-time PA levels. The intention for PA practice showed no moderating effects on leisure PA. Social support from friends was associated with achieving recommended PA levels (≥150min/week), regardless of intention for PA practice (PR: 1.45; 95% CI: 1.09-1.93). In this study, moderating effect of intention for PA practice on the association between social support and leisure-time PA has not been found.